2003
DOI: 10.1007/s10310-002-0024-9
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and inter-storm oxygen-18 and deuterium variations of rain, throughfall, and stemflow, and two-component hydrograph separation in a small forested catchment in Japan

Abstract: Inter-and intra-storm oxygen-18 variations in rain, throughfall, and stemflow were measured to estimate accurate "new" water inputs to the watershed within a 0.84-ha watershed planted with 80-year-old Cryptomeria japonica and Chamaecyparis obutusa artificial forest at the Hitachi Ohta experimental watershed in Japan. In addition two-component hydrograph separation using oxygen-18 concentrations was conducted with four types of "new" water concentration: (1) incremental volume-weighted mean concentrations of ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 27 publications
5
61
0
1
Order By: Relevance
“…On the other hand, stemflow isotopic characteristics especially for oxygen and hydrogen isotopes are poorly understood. Kubota and Tsuboyama (2003) compared isotopic composition of throughfall and stemflow water collected by bulk sampling during a rainfall event and reported that the oxygen isotopic composition in stemflow is higher than that in throughfall, though no specific reasons were given for the isotopic differences.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, stemflow isotopic characteristics especially for oxygen and hydrogen isotopes are poorly understood. Kubota and Tsuboyama (2003) compared isotopic composition of throughfall and stemflow water collected by bulk sampling during a rainfall event and reported that the oxygen isotopic composition in stemflow is higher than that in throughfall, though no specific reasons were given for the isotopic differences.…”
Section: Introductionmentioning
confidence: 99%
“…End-member mixing models can calculate contributions of different water sources when the isotope value of each water source can be determined [11,26]. During the sampling period, the rainfall event of August 15, 2003 (14.8 mm/day) was used to calculate its contribution in sequential 5 days (August [16][17][18][19][20] since there had few rainfalls from August 14 to 20 except for August 15. Two-source mixing model with single isotope is used to calculate the contributions of two sources, as follows: …”
Section: Discussionmentioning
confidence: 99%
“…The water stable isotope ratios can benefit for analyzing water flux variations through the ecosystem or plant individual [9][10][11][12], such as plant water use [13][14][15][16], stemflow, throughfall, and evaporation rate [17,18]. At a large scale, the rain forest plays an important role in the regional hydrological cycle by stable isotope analysis [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, by measuring the stable isotope ratio, runoff water and event rainwater can be separated into two components: pre-event water and event water [17][18][19]. Many reports describe the simultaneous observations of dissolved ion concentration and stable isotope ratio in runoff water [20,21]; however, only a few studies report simultaneous observations of SS concentration and stable isotope ratio in runoff water.…”
Section: Introductionmentioning
confidence: 99%